(untitled) (Journal of the Bangladesh Agricultural University, 2017)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during June to December, 2013 to investigate the response of some short duration aman rice varieties to date of transplanting. The experiment consisted of three transplanting dates viz. 26 July, 5 August and 15 August and seven short duration T. aman rice varieties viz. BRRI dhan33, BRRI dhan39, BRRI dhan49, BRRI dhan56, BRRI dhan57, BRRI hybrid dhan4 and Binadhan-7. The experiment was laid out in split plot design with three replications. Transplanting dates were allocated into the main plot and varieties into the sub plot. Results indicate that Binadhan-7 produced the highest grain yield (4.90 t ha1), straw yield (5.58 t ha1), biological yield (10.44 t ha1), and harvest index (47.10%). Lowest grain yield (3.27 t ha1), straw yield (3.96 t ha1) and biological yield (7.20 t ha1) were produced by BRRI dhan57. BRRI dhan49 had taken the longest field duration (120 DAT) while BRRI dhan57 had taken the shortest field duration (88 DAT). Plant height (119.12 cm), number of total tillers m-2 (276.40), number of effective tillers m2 (260.02), number of grains panicle1 (109.19), grain yield (4.75 t ha1), straw yield (5.22 t ha1), biological yield (9.97 t ha1) and harvest index (47.64%) were highest on 26 July transplanting; decreased on 5 August transplanting and drastically declined on 15 August transplanting. The present study concludes that the highest yield for short duration T. aman rice cultivation could be possible by Binadhan-7 transplanting on 26 July. J. Bangladesh Agril. Univ. 15(1): 1-6, January 2017